Analysis and Design of a Web-Based Online Booking System for Laboratory Examination Services - Nathanael, Jovan Arsenio; Kuswanto, Verri (bit-Tech, 2026)
The laboratory examination registration process in many clinics is still conducted manually, resulting in inefficiencies, limited accessibility, and fragmented data management. This study aims to design and evaluate an online laboratory examination booking system to address these limitations and improve service accessibility. The system was developed using a prototype-based approach, enabling iterative refinement through continuous user feedback during the design and evaluation stages. This approach supports early validation of system requirements and functional suitability when compared to conventional linear development methods. The proposed system provides integrated access to laboratory examination information, including available examination types, pricing, schedules, and downloadable examination results, which can be accessed anytime and anywhere without requiring patients to revisit the clinic. System evaluation was conducted through usability testing involving patients and officers using the System Usability Scale. The results indicate high usability levels, with patients achieving a score of 91% and officers achieving 92%, reflecting excellent system acceptance and ease of use. These findings demonstrate measurable improvements in registration efficiency and user satisfaction compared to the previous manual process. Furthermore, the application of the prototype method proved effective in identifying functional gaps at an early stage, resulting in a more user-centered and adaptable system design. This study contributes a practical solution for improving laboratory examination registration services and empirical evidence supporting the effectiveness of prototype-based development in healthcare information systems.